2008
DOI: 10.1158/1078-0432.ccr-07-5237
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity at the BRCA2 Locus Detected by Multiplex Ligation-Dependent Probe Amplification is Common in Prostate Cancers from Men with a Germline BRCA2 Mutation

Abstract: Purpose: Prostate cancer risk is increased for men carrying a pathogenic germline mutation in BRCA2, and perhaps BRCA1. Our primary aim was to test for loss of heterozygosity (LOH) at the locus of the mutation in prostate cancers from men who a carry pathogenic germline mutation in BRCA1 or BRCA2, and to assess clinical and pathologic features of these tumors. Experimental Design: From 1,243 kConFab families: (a) 215 families carried a pathogenic BRCA1 mutation, whereas 188 families carried a pathogenic BRCA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 42 publications
3
30
1
Order By: Relevance
“…13). Furthermore, this study confirmed our previously published data that loss of heterozygosity is observed in the tumor tissue of the majority of BRCA2 carriers (6). While this study demonstrates that a BRCA2 mutation is an independent factor in overall survival, it does so in a group of men unselected for family history.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…13). Furthermore, this study confirmed our previously published data that loss of heterozygosity is observed in the tumor tissue of the majority of BRCA2 carriers (6). While this study demonstrates that a BRCA2 mutation is an independent factor in overall survival, it does so in a group of men unselected for family history.…”
Section: Introductionsupporting
confidence: 91%
“…Early studies estimated the relative risk for developing prostate cancer in men from BRCA2 mutation carrier families as being 2.9 to 4.8 (3)(4)(5), with some subgroups (men <65 years) having a relative risk as high as 7.3 (3). Later studies, estimated that men with a pathogenic BRCA2 mutation are at 3.5-fold (95% CI: 1.8-12) increased risk of developing prostate cancer (6). Furthermore, prostate cancers arising in BRCA2 mutation carriers display an aggressive tumor phenotype (6)(7) and present as more poorly differentiated tumors when compared with noncarrier prostate cancer controls (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The inheritance of one defective allele confers PCa predisposition; and neoplastic cells from predisposed individuals frequently exhibit loss of heterozygosity in the remaining wild-type allele, 4 consistent with a critical role of BRCA2 in prostate tumor suppression. The major identified function of the BRCA2 protein is to form complexes with Rad51 in the nuclei, which orchestrate homologous recombinational repair of double-stranded DNA breaks.…”
mentioning
confidence: 83%
“…28 These reports suggest that pathogenic mutations in BRCA1 and BRCA2 are more common in pediatric cancer than has been recognized previously and that they potentially underpin a broader spectrum of cancer phenotypes. [28][29][30][31][32][33][34][35][36][37][38] Family history is commonly used to identify persons with a possible heritable predisposition, especially within the pediatric cancer population. 39 However, only 40% of our patients with germline mutations that were pathogenic or probably pathogenic and that could be evaluated had a family history of cancer.…”
Section: Discussionmentioning
confidence: 99%